2019
DOI: 10.1103/physreva.99.062327
|View full text |Cite
|
Sign up to set email alerts
|

Information backflow as a resource for entanglement

Abstract: The issue of whether non-Markovianity (NM) could be considered as a resource in quantum information has been a subject of intense debate for the last years. Recently, a simple mechanism was proposed in which one of the main features of NM, the backflow of information from the environment to the system, represents a fundamental and quantifiable resource for generating entanglement within an open quantum system coupled to a finite and small environment [N. Mirkin, P. Poggi and D. Wisniacki, Phys. Rev. A, 99(2), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…We may define the ratio of the qubit 1-qubit 2 coupling to the qubit 2-field as k ≡ g/λ, and rewrite (21) and (22) in terms of k…”
Section: The Relevant Matrix Elements In Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…We may define the ratio of the qubit 1-qubit 2 coupling to the qubit 2-field as k ≡ g/λ, and rewrite (21) and (22) in terms of k…”
Section: The Relevant Matrix Elements In Equationmentioning
confidence: 99%
“…In fact, even a single uncontrollable subsystem coupled to the system of interest may cause a considerable disturbance. As examples of possible minimal environments, we may cite spins [20,21], a single two level system [22,23,24] and one or two modes of the quantized electromagnetic field [25,26,27,28]. In summary, we may be facing multiple challenges regarding the study of coupled quantum systems immersed in environments that might also be of different sizes, and in which the perturbative methods normally employed, e.g., local approaches, may not be applicable.…”
Section: Introductionmentioning
confidence: 99%
“…By taking the time derivative on the above equation, we find that the condition for breaking the monotonicity of the functionC(t) is given by the sign of dΓ(t)/dt, that matches the one obtained for the incoherent case Ω = 0, see Eq. (7). Therefore, we conclude that the functionC(t) is a monotonically decreasing function in time if the reduced dynamics is Markovian, i.e.…”
Section: A Coherent Maps In the Weak-coupling Regimementioning
confidence: 65%
“…To implement efficient error-mitigation schemes it is crucial to have a precise understanding of the underlying system-environment interaction [4], in particular in realistic non-Markovian settings, where information can flow back from the bath to the system and is not immediately lost. These scenarios have been exploited, for example, for quantum metrology [5], quantum channels [6], entangling protocols [7] or quantum control [8] and led to a growing interest in the questions how different environments can be compared and how non-Markovianity (NM) can be quantified [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it appears that non-Markovianity is the norm rather than the exception; it must be accounted for in real quantum computers [16], in quantum metrology with noisy environments [17], and in many realistic quantum control tasks [18]. Furthermore, several researchers have suggested that non-Markovianity may be useful for certain tasks: it has been shown to improve the performance of quantum heat engines [19,20], enhance quantum control [18,[21][22][23], reduce decoherence [24] and allow the perfect teleportation of mixed states [25]. However, there is no consensus on how to treat temporal correlations as a resource.…”
Section: Introductionmentioning
confidence: 99%